Vulnerabilidades da população LGBTQIA+ relacionadas às infecções sexualmente transmissíveis e ao consumo de drogas - Souza, Izabel Cristina de (2021)
The study aimed to understand the vulnerabilities of the LGBTQIA+ population to sexually transmitted infections/HIV (STI) and their involvement with drugs. Observational research, with a cross-sectional, quantitative and correlational, descriptive and analytical approach. Participants were Brazilians aged 18 years or older, self-reported LGBTQIA+ with at least one sexual encounter in the last twelve months. For data collection we used an survey with information about sociodemographic data, knowledge about HIV, access to health services, STI testing and sexual behavior, and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) to verify drug involvement. Data were organized and analyzed using the Statistical Package for the Social Sciences (SPSS) v.23.0 for Windows® software, calculating absolute and relative frequencies, confidence intervals and applying the Kruskal-Wallis, chi-square and Fisher statistical tests. The research was approved by the Research Ethics Committee of the Federal University of Ceará, with approval number 3.921.161. The sample was composed of 254 participants, aged 18 to 25 years (78.7%), male (54.6%), cisgender (91.7%), homosexual (57.1%), and brown skin color (33%). Most were single (51.2%) and had no children (98%), and the main occupation was student (56.6%) with incomplete higher education (52.8%). There was an association between STI diagnosis and having children, which was a protective fact (p=0.036; OR: 8.81). Most had sufficient knowledge about HIV (75.6%). Condoms and lubricants were more commonly purchased (38.2%; 42.9%) and STI testing was performed by the majority (56.7%). The main place of care was private practice (56.6%). Performing tests in the last year and signs of STI were associated with STI diagnosis (p<0.01). Fixed partnerships (63.4%) were more reported and this group used condoms less. As for drug use, involvement was higher with alcohol (80.7%), tobacco (59.4%) and marijuana (59%). As for the risk for developing dependence, most were classified as moderate (54.8%). Marital status (p=0.01), current housing (p=0.01), and religion (p<0.01) were related to the degree of drug dependence. The individual vulnerabilities most identified were low self-perception of risk, non-use of condoms, chemical sex, and multiple sexual partnerships. The social vulnerabilities were: ease of acquiring drugs, stigma and prejudice, influence of friends or lack of social support. The programmatic vulnerabilities were: weakening of programs to confront HIV/AIDS, sexually transmitted infections, and support to people who use drugs, and loss in services regarding human and material resources.